Ideal Beauty Representation: Multimodality Analysis of Scarlett Whitening’s Content with Song Joong-Ki - Silvia, Atika; Syawal, Marsaa Salsabila; Pinem, Meyka Septira Utami; Hanum, Ratu Suud (UPT Publikasi Ilmiah UNISBA, 2024)
Advertising as a form of communication is considered an effective tool to promote sales. According to the stereotype in the public, beauty brands usually are represented by women. For Scarlett Whitening's advertisement, Song Joong-Ki is chosen as their ambassador even though there is still a stereotype of men’s role, especially in advertisements. This research aims to describe modality and analyze ideational, interpersonal, and compositional meta-functions in collaboration content between Scarlett Whitening and Song Joong-Ki. This research was conducted with a qualitative approach and using multimodality methods by Kress & Van Leeuwen (2006) with the type of social semiotics research. The results show that Song Joong-Ki invites the audience to focus on the product, shows a close relationship with the audience, and shows his love for the product and the audience. Scarlett Whitening emphasizes the representation of beauty standards, the Pan-Asian Look, which is identical to clean white skin, marketed and represented visually with Song Joong-Ki as the primary focus. Results also demonstrated Song Joong-Ki's usage of beauty products as a male in the campaign and that the marketer may use his status as a Korean actor to employ Parasocial contact with his fans as market targets.